2011
DOI: 10.1016/j.neuron.2011.10.010
|View full text |Cite
|
Sign up to set email alerts
|

ELP3 Controls Active Zone Morphology by Acetylating the ELKS Family Member Bruchpilot

Abstract: Elongator protein 3 (ELP3) acetylates histones in the nucleus but also plays a role in the cytoplasm. Here, we report that in Drosophila neurons, ELP3 is necessary and sufficient to acetylate the ELKS family member Bruchpilot, an integral component of the presynaptic density where neurotransmitters are released. We find that in elp3 mutants, presynaptic densities assemble normally, but they show morphological defects such that their cytoplasmic extensions cover a larger area, resulting in increased vesicle tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 54 publications
1
75
0
Order By: Relevance
“…However, the regulatory effect of the elongator complex on ␣-tubulin acetylation is controversial. Recent research showed that a deficiency in ELP3, which is the catalytic subunit of elongator complex, did not decrease the level of ␣-tubulin acetylation in cell lines and cortical neurons (Mioekiewicz et al, 2011). Whether ␣-tubulin acetylation underlies the migratory defect in ELP3-deficient neurons needs to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…However, the regulatory effect of the elongator complex on ␣-tubulin acetylation is controversial. Recent research showed that a deficiency in ELP3, which is the catalytic subunit of elongator complex, did not decrease the level of ␣-tubulin acetylation in cell lines and cortical neurons (Mioekiewicz et al, 2011). Whether ␣-tubulin acetylation underlies the migratory defect in ELP3-deficient neurons needs to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The elongator complex comprises six proteins, ELP1-6, and is responsible both for histone acetylation to facilitate transcription and for the modification of the wobble position U-34 of eukaryotic tRNAs by carbamoylmethylation or methoxy-carbonylmethylation at C-5 of uridine (35,36). ELP3 contains both radical SAM and histone acetyltransferase domains.…”
Section: Discussionmentioning
confidence: 99%
“…95,96 An explanation for the neurodevelopmental defects in D. melanogaster could be that Elongator complex acetylate Bruchpilot, a protein important for neuronal differentiation. 97 Both in mice and C. elegans, the Elp3p homolog has been implicated in acetylating lysine 40 (K40) in a-tubulin. 98,99 However, the C. elegans elpc-3 mutant did not have a defect in a-tubulin K40 acetylation.…”
Section: Elongator Complex In Multicellular Eukaryotesmentioning
confidence: 99%